Application of organic matter-enriched biochar for improving degraded acid sulfate soil properties in rice (Oryza sativa L.) cultivation - Masulili, Agusalim; Rahayu, Sri; Suci, Ida Ayu; Kurniadi, Edi (Brawijaya University, 2026)
Acid sulfate soils pose significant challenges for rice cultivation due to their extreme acidity (pH<4.0) and associated nutrient deficiencies. This study investigated the effectiveness of biochar enriched with various organic amendments in improving soil properties and rice growth in degraded acid sulfate soils. A randomized block design was employed with seven treatments: control (B0), biochar enriched with Chromolaena odorata (B1), rice straw (B2), chicken manure (B3), cattle manure (B4), Tithonia sp. compost (B5), and NPK fertilizer at half the recommended dose (B6), each applied at 10 t/ha. The experiment was conducted under greenhouse conditions using 10 kg of soil per polybag with four replications. Soil samples from Sungai Kakap, West Kalimantan, exhibited severe constraints, including pH levels of 3.75-3.87, organic carbon content of 0.82-0.98%, and high Al and Fe contents (>3%). Results demonstrated that organic matter-enriched biochar treatments significantly improved soil chemical properties (p<0.01). Rice straw-enriched biochar (B2) achieved the highest available P (117.93 ppm) and K (1.09 cmol(+)/kg), while cattle manure-enriched biochar (B4) showed maximum organic C increase (1.30%). Plant growth parameters showed significant improvement, with B2 producing the tallest plants (137.43 cm) and B5 (Tithonia sp.) yielding the highest productive tillers (38.83). The findings indicate that biochar enriched with local organic materials, particularly rice straw and Tithonia sp., offers a sustainable solution for rehabilitating degraded acid sulfate soils while enhancing rice productivity.